(untitled) (International Association of Biologicals and Computational Digest, 2023)
Xeriscaping is the process of landscaping or gardening that reduces or eliminates the need for supplemental water from irrigation. Xeriscaped landscapes can reduce water use by up to 60% or more compared to regular lawn landscapes. Our irrigated landscapes provide us with many benefits that include beautiful surroundings, natural cooling, and the cleansing of our environment. Xeriscape gardens are the perfect way to Live Green. In this review paper, the establishment and benefits of Xeriscape gardens have been discussed and trees that are suitable for Xeriscape gardens in the Indian context have been enlisted along with their landscape use. This can be achieved by the ideal usage of water by selecting suitable techniques either the irrigation system or reusing water, and by the proper management of landscape architecture and its requirements.